WORK FLEXIBILITY AND SATISFACTION: KEY PREDICTORS OF PRODUCTIVITY IN THE WORKPLACE - Fadillah, Yuni; Qodriah, Sari Laelatul; Risdianto, Risdianto (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study explores the influence of Flexible Working Arrangements (FWA) and Job Satisfaction on employee productivity. As workplaces evolve and adapt to post-pandemic conditions, organizations are increasingly implementing flexible work systems to improve efficiency and effectiveness. FWA provides employees the flexibility to manage their work hours and locations, while job satisfaction reflects their contentment with roles, compensation, opportunities for growth, supervision, and workplace relationships. Understanding the impact of these factors is essential for enhancing organizational performance through human resource strategies that prioritize employee well-being and autonomy.Methods: The research employs a quantitative approach, using a descriptive associative method. The study involves 36 employees, using a saturation sampling technique where the entire population is used as the sample. Data were collected through structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 22.Results: Findings. The findings show that Flexible Working Arrangements and Job Satisfaction significantly and positively influence employee productivity, both partially and simultaneously. Flexibility in work schedules and locations contributes to improved performance, while job satisfaction arising from positive work conditions and relationships further enhances productivity. These results suggest that adopting flexible work models and fostering job satisfaction are key strategies to improve employee productivity. Organizations aiming to remain adaptive and competitive should consider these aspects in designing modern and responsive work policies. Keywords: Flexible Working Arrangement, Job Satisfaction, Work Productivity